Natural variability or climate change? Stakeholder and citizen perceptions of extreme event attribution. (May 2020) - Osaka, Shannon; Bellamy, Rob
Highlights: Perceptions of EEA were explored via interviews with key stakeholders and citizen focus groups. The California drought was a unique case of EEA owing to the large number of attribution studies. Policymakers were largely ambivalent about the usefulness of EEA. In focus groups, divergent EEA results reinforced existing views on climate change. Communication of EEA requires attention to the role of methodology in shaping results. Abstract: Scientists can now connect extreme weather events with climate change using a methodology known as "extreme event attribution", or EEA. The idea of connecting climate change and extreme weather has long been heralded as a panacea for communications, connecting the dangers of climate change to real-world, on-the-ground events. However, event attribution remains a nascent science, and attribution studies of the same event can sometimes produce divergent answers due to precise methodology used, variables examined, and the timescale selected for the event. The 2011–2017 California drought was assessed by 11 EEA studies which came to varying conclusions on its connection to climate change. This article uses the case study of the drought and a multi-methods approach to examine perceptions of EEA among key stakeholders and citizens. Twenty-five key informant interviews were conducted with different stakeholders: scientists performing EEA research, journalists, local and state-level policymakers, and non-governmental organization representatives. In addition, two focus groups with 20 California citizens were convened: one with environmentalists and another with agriculturalists. While climate change was viewed by many as a mild contributing factor to the California drought, many stakeholders had not heard of EEA or doubted that scientists could conclusively link the drought to anthropogenic climate change; those that were familiar with EEA felt that the science was generally uncertain. In the focus groups, presentation of divergent EEA results led participants to revert to pre-existing ideas about the drought-climate connection, or to question whether science had sufficiently advanced to analyze the event properly. These results indicate that while EEA continues to provoke interest and research in the scientific community, it is not currently utilized by many stakeholders, and may entrench the public in pre-existing views.